A case report of severely damaged hip joint caused by SAPHO syndrome treated with 2-stage total hip arthroplasty. Issue 27 (July 2016) - Yeo, Ingwon; Cha, Hoon-Suk; Yoon, Young Cheol; Park, Youn-Soo; Lim, Seung-Jae
Abstract: Introduction: Synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome is an increasingly recognized entity. The hip joint is known as a less frequently affected site in SAPHO syndrome, and there has been limited reports about hip joint diseases caused by SAPHO syndrome, and as such adequate treatment for this disease spectrum is still not fully elucidated. Case: We describe the case of a 52-year-old man admitted for SAPHO syndrome who went on to be diagnosed with advanced secondary hip arthritis associated with disabling right hip pain. The diagnosis of SAPHO syndrome was delayed; the patient was given a clinical diagnosis of osteomyelitis and treated with prolonged courses of antibiotics and open surgical debridement at previous tertiary health facility. The patient underwent 2-stage joint replacement surgery in our hospital. At 1 year after the surgery, he is well, with minimal right hip pain and the prosthesis is functioning well. Conclusion: This case shows the safety and effectiveness of the 2-stage joint replacement in treating destructive hip disease caused by SAPHO syndrome mimicking infectious arthritis.